Community Empowerment in Waste Management through the Pede Message Program in Cemenggaon Traditional Village, Gianyar Regency, Bali Province - Ridwan, Ridwan; Wijaya, I Made Aldy (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
In terms of waste management, Gianyar Regency still lacks access to facilities and infrastructure in reaching certain sub-districts to certain villages. In addition, the lack of knowledge about the impact of waste and how to manage it as well as the benefits obtained by the community in the waste management process is also a factual problem in Gianyar Regency. The Gianyar Regency Government, of course, is well aware of the waste problem so it is considered necessary to have a waste management system that is overcome starting from the upstream. This study aims to find out community empowerment in managing waste through the Pesan Pede program, inhibiting factors and efforts to overcome inhibiting factors in community empowerment in managing waste through the Pesan Pade program in Cemenggaon Traditional Village, Gianyar Regency. The method used is a descriptive qualitative research design. Data collection was carried out by semi-structured interviews, observations, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of empowerment in waste management through the PESAN PEDE program in Customary Villages has been carried out well. This is marked by the activities carried out by the Village Government through the Cemenggaon Traditional Village Waste Management Agency, Celuk, Gianyar Regency, Bali Province. The inhibiting factors in the implementation of this empowerment are the community's lack of understanding in managing waste, the limitations of processing tools, and the application of waste banks that are not optimal. The efforts made to overcome the inhibiting factors are the implementation of education, holding regular meetings, increasing the capacity of the Waste Management Agency management, and optimizing waste transportation facilities.